2000
DOI: 10.4049/jimmunol.165.4.2142
|View full text |Cite
|
Sign up to set email alerts
|

E-Selectin-Dependent Signaling Via the Mitogen-Activated Protein Kinase Pathway in Vascular Endothelial Cells

Abstract: E-selectin, a cytokine-inducible adhesion molecule, supports rolling and stable arrest of leukocytes on activated vascular endothelium. Previous studies have suggested that this transmembrane protein can also transduce signals into the endothelial cell. We now demonstrate activation of the mitogen-activated protein kinase (MAPK) signaling cascade in cultured HUVEC in response to E-selectin-dependent leukocyte adhesion and Ab-mediated cross-linking of cell surface E-selectin. Adhesion of increasing numbers of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 50 publications
4
62
0
3
Order By: Relevance
“…The notion that E-selectin induces a forward signalling in endothelial cells has previously been supported by studies showing that the adhesion of LS174T colon adenocarcinoma to E-selectin-expressing HUVEC initiate the endocytosis of E-selectin (Burdick et al, 2003). It is also supported by studies reporting that activation of E-selectin by crosslinking activating antibodies or adhesion of HL-60 leukaemia cell induces the clustering of E-selectin and triggers the activation of ERK and p38 in endothelial cells (Yoshida et al, 1996;Hu et al, 2000Hu et al, , 2001Yoshida et al, 2003). Activation of ERK derives from the phosphorylation of Tyr603 within E-selectin by an unknown kinase (Hu et al, 2001).…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…The notion that E-selectin induces a forward signalling in endothelial cells has previously been supported by studies showing that the adhesion of LS174T colon adenocarcinoma to E-selectin-expressing HUVEC initiate the endocytosis of E-selectin (Burdick et al, 2003). It is also supported by studies reporting that activation of E-selectin by crosslinking activating antibodies or adhesion of HL-60 leukaemia cell induces the clustering of E-selectin and triggers the activation of ERK and p38 in endothelial cells (Yoshida et al, 1996;Hu et al, 2000Hu et al, , 2001Yoshida et al, 2003). Activation of ERK derives from the phosphorylation of Tyr603 within E-selectin by an unknown kinase (Hu et al, 2001).…”
Section: Discussionmentioning
confidence: 81%
“…We next verified whether the adhesion of colon cancer cells HT-29 to HUVEC also initiated the activation of E-selectin and then of ERK and p38 in the endothelial cells. In this set of experiments, HT-29 cells were previously fixed with 2% paraformaldehyde to highlight the activation of the MAP kinases of solely endothelial cells (Hu et al, 2000;Laferrie`re et al, 2004). Then, fixed HT-29 cells were added to E-selectin-expressing HUVEC for increasing intervals of time and the activation of p38 and ERK was determined.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In flow-free conditions, adhesion of leukocytes to cytokine-activated endothelial cells induces association of E-selectin with lipid raft domains, cytoskeletal components, and signaling molecules. [23][24][25][26][27] Indeed, it has been suggested that E-selectin is primarily associated with lipid rafts even before it engages leukocytes. 27 If this were true, E-selectin would probably not cluster in clathrin-coated pits, as lipid rafts are not known to mix with clathrin-enriched structures.…”
Section: Introductionmentioning
confidence: 99%